BEAUTY IN MATHEMATICAL EDUCATION: SYNERGETIC WORLDVIEW - V. A. Testov (Russian State Vocational Pedagogical University, 2019)
Introduction. The most important concepts underlying beauty are the mathematical concepts of symmetry and fractality. These categories are fundamental for modern mathematics, science and culture in general. However, in mathematical education and pedagogical literature, the ratio of these main categories has not been considered yet. Of special interest is the fact that the concepts of fractals, fractality and fractal geometry and fractal graphics are not included in the vast majority of high school programmes, although they have become commonly used among mathematicians and graphic designers.The aims of the article were the following: to demonstrate intersectionality and correlations of the basic concepts of symmetry and fractals from the point of view of synergetics, to establish the relevance of studying these concepts in the course of mathematics for aesthetic education of students and development of their worldview.Methodology and research methods. A significant role in the study is given to post-non-classical methodology based on synergetic worldview. The author employed the provisions of trinitarian methodology: in addition to two binary oppositions, the third element is necessary to solve the problem of contradiction of theseoppositions and integration into one coherent whole as the onditions of their coexistence. In the course of the research, analysis and generalisation of pedagogical and methodical literature, methods of comparative, historical and logical types of analysis were used.Results and scientific novelty. For centuries, beauty has been understood as a stable order and symmetry. The synergetrics as a general scientific theory about self-organisation of complex systems allows us to give another interpretation of beauty - as a kind of attractor, the result of self-organisation of nature or theflight of human thought. In the most general view, symmetry can be considered as transformation of similarity, which is also the core of another concept - fractality. On the one hand, fractality can be considered as one of the manifestations of symmetry in the broad sense. On the other hand, symmetry can be considered as a manifestation of fractality with a finite number of iterations. Thus, the concepts of symmetry and fractality are closely interrelated. Symmetry and fractality are two opposites, mutually complementing each other, aesthetically and mathematically  mutually passing into each other. Symmetry reveals the beauty of a sustainable order and fractality reflects the beauty of the result of self-organisation of the chaos of nature or the freedom of the human mind. Therefore, symmetry and fractals are the most important concepts for the disclosure of the beauty of the universe, which determines their importance for mathematical learning and for aesthetic education of students.Practical significance. Taking into account the fact that the concepts of symmetry and fractals are directly related to each other, they should be jointly-taught. This will contribute to the development concept of mathematics education: to increase motivation for mathematical studies, to develop cognitive interests and activities, to narrow the gap between education and research processes, to overcome the problems with aesthetic education of students.